Glorifying Human Virtues and Condemning Corruption in Ahmad Yasawi’s “Diwan-i Hikmat” - Juraev, Zuhriddin; Rajavaliev, Boburjon (Journal of History Culture and Art Research, 2022)
The famous Sufi Ahmad Yasawi is a Central Asian great mystic who founded Sufi poetry in the literature of Turkic peoples. Yasawi’s work “Diwan-i Hikmat” is a comprehensive work that discusses pure Islamic teachings and Sufi tradition in a poetic way. This study aims to literary observe some verses from “Diwan-i Hikmat”. As a contribution to Sufi poetry and Sufi literature studies, this article examines the glorification of human virtues and the condemnation of vices such as impurity, ignorance, and worldliness in the “Diwan-i Hikmat”. During the literary analysis of the poems, Yasawi’s instructions to repent, achieve good, and avoid corruption are considered based on the lines of “wisdom” poems as they relate to morality. Finally, this study ends by emphasizing Yasawi’s work is still relevant for shaping personality perfection.